2004
DOI: 10.1007/s00436-004-1273-7
|View full text |Cite
|
Sign up to set email alerts
|

Presence of Trichobilharzia szidati in Lymnaea stagnalis and T. franki in Radix auricularia in northeastern France: molecular evidence

Abstract: A molecular approach was used to analyse a focus of cercarial dermatitis in northeastern France (Lake Der-Chantecoq), including both cercariae and snails,by sequencing the internal transcribed spacers (ITS1 for ocellate furcocercariae and ITS2 for snails). Lymnaea stagnalis were found infected with the furcocercariae of Trichobilharzia szidati, and T. franki furcocercariae were found in Radix auricularia. The record of these two visceral parasites of birds in northern France confirms strong host-parasite relat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(35 citation statements)
references
References 20 publications
1
34
0
Order By: Relevance
“…Most of the effort has been conducted using three gene regions. To date, the nuclear ribosomal DNA D1-D2 regions of 28S, the internal transcribed spacer (ITS) region, and the mitochondrial cox1 gene have been tested as molecular markers for systematics (40,63,67,69,70,105,123,248,249,251), epidemiology (252), and diagnostics (121,253). Sequencing of gene regions such as the nuclear ITS region and the mitochondrial cox1 gene not only has linked life cycle stages but also has suggested that our recognition of the diversity of avian schistosomes continues to grow (10, 12, 40, 65-67, 69, 70, 105, 129, 133, 135).…”
Section: Detection and Identification Of Avian Schistosomesmentioning
confidence: 99%
“…Most of the effort has been conducted using three gene regions. To date, the nuclear ribosomal DNA D1-D2 regions of 28S, the internal transcribed spacer (ITS) region, and the mitochondrial cox1 gene have been tested as molecular markers for systematics (40,63,67,69,70,105,123,248,249,251), epidemiology (252), and diagnostics (121,253). Sequencing of gene regions such as the nuclear ITS region and the mitochondrial cox1 gene not only has linked life cycle stages but also has suggested that our recognition of the diversity of avian schistosomes continues to grow (10, 12, 40, 65-67, 69, 70, 105, 129, 133, 135).…”
Section: Detection and Identification Of Avian Schistosomesmentioning
confidence: 99%
“…This number of reference sequences would be sufficient for distinct species specific clades to emerge during phylogenetic analysis and definitively identify sequences generated in this current study. Each of these reference sequences was considered as putative throughout the analysis and were chosen because they were generated for studies focused primarily on the molecular identification and the evolutionary relationships of Radix species particularly from the following works: Albrecht et al, 2009;Bargues et al, 2001;Bolotov et al, Christiansen et al, 2014;Cipriani et al, 2011;Correa et al, 2011;Dung et al, 2013;Ferreira et al, 2014;Ferté et al, 2005;Huňova et al, 2012;Jouet et al, 2008Jouet et al, , 2010Kaset et al, 2009;Liu et al, 2010;Patel et al, 2015;Pfenninger et al, 2011;Novobilsky et al, 2014;Schniebs et al, 2011Schniebs et al, , 2013Vinarski et al, 2015;von Oheimb et al, 2011; Therefore the sequences used for inter-species comparisons were considered to be representative of taxa alone and were not used to make biogeographical inferences.…”
Section: Collectionmentioning
confidence: 99%
“…Therefore, knowing that exclusively R. balthica occurs in Iceland, some schistosomes already reported to infect Palaearctic birds are regarded not to be able to complete their life cycle in the country. Thus, T. szidati that develops in Lymnaea stagnalis (Neuhaus 1952;Ferté et al 2005;Semyenova et al 2005) should not be able to develop Fig. 2 Average egg sizes and ±SD (bars) of seven morphologically distinct egg types (Fig.…”
Section: European Radix Species and Their Ocellate Furcocercariae Infmentioning
confidence: 99%